A reflective characterisation of occasional user. - Carrillo-León, Antonio Luis; Santiago, Martinez; Falgueras-Cano, Juan; Scott-Brown, Kenneth C. (Elsevier, 2016)
This work revisits established user classifications and aims to characterise a historically unspecified user category, the Occasional User (OU). Three user categories, novice, intermediate and expert, have dominated the work of user interface (UI) designers, researchers and educators for decades. These categories were created to conceptualise user's needs, strategies and goals around the 80s. Since then, UI paradigm shifts, such as direct manipulation and touch, along with other advances in technology, gave new access to people with little computer knowledge. This fact produced a diversification of the existing user categories not observed in the literature review of traditional classification of users. The findings of this work include a new characterisation of the occasional user, distinguished by user's uncertainty of repetitive use of an interface and little knowledge about its functioning. In addition, the specification of the OU, together with principles and recommendations will help UI community to informatively design for users without requiring a prospective use and previous knowledge of the UI. The OU is an essential type of user to apply user-centred design approach to understand the interaction with technology as universal, accessible and transparent for the user, independently of accumulated experience and technological era that users live in.
ôlítica de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/12514
Keywords: Ingeniería del software; Interfaces de usuario; Sistemas hombre-máquina; User classification; Occasional use; User models; HCI theory; Concepts and models; Occasional user